Husserl and Weyl on the Constitution of Space The Role of Symbolic Knowledge - Silva, Jairo José da [UNESP] (Springer Nature, 2019)
I discuss in this paper Husserl and Weyl’s views on the role of intuition and symbolization in empirical science and their reactions to purely symbolic extensions of mathematical representations of empirical reality. Although both accept that physical space as considered in mathematical physics, for instance, is an intentional construct out of perceptual space that eliminates subjective content of perceptual experience in favor of objective form, thus transforming space as perceived in an empty mathematical manifold, they differ as to the freedom allowed to mathematics to further elaborate this and other mathematical representatives of perceptual reality. Husserl puts serious restrictions to non-eliminable, non-denoting symbolic extensions of representing manifolds, which Weyl, in his more holistic approach, is willing to accept.